Quetiapine and olanzapine misuse prevalence in a US general population sample - Kirk E Evoy, PharmD, BCACP, BC-ADM, CTTS; Shelby Humpert, PharmD; Sorina Torrez, PharmD; Haneen Hussein, PharmD; Jordan R Covvey, PharmD, PhD, BCPS (American Association of Psychiatric Pharmacists, 2023)
Introduction: Second-generation antipsychotics (SGA) are associated with misuse potential; however, there are limited data describing the prevalence and characteristics of this misuse. This study was conducted to identify and describe quetiapine and olanzapine misuse among US adults. Methods: This cross-sectional survey questionnaire was conducted online using Qualtrics research panel aggregator service to identify a quota-based sample of respondents constructed to mimic the general US population aged 18 to 59 years, with regards to gender, geographic region, ethnicity, income, and education level. Misuse was defined as using quetiapine or olanzapine for treatment outside of medical recommendations, for reasons other than a diagnosed medical condition, or obtaining without a prescription. A logistic regression was used to identify factors associated with SGA misuse, incorporating relevant covariates. Results: Among 1843 total respondents, 229 had a history of quetiapine or olanzapine use. Misuse prevalence was estimated to be 6.3% (95% CI: 5.2, 7.5%). Although most respondents (?70%) using quetiapine or olanzapine reported doing so to treat a diagnosed medical condition, those misusing them most commonly did so because prescribed medications failed to relieve their symptoms. Misuse was commonly reported (?50%) concomitantly with opioids, benzodiazepines, or alcohol. Factors significantly associated with quetiapine or olanzapine misuse included employment (OR = 4.64), previous substance use disorder treatment (OR = 2.48), and having riskier attitudes toward medication misuse (OR = 1.23). Discussion: Misuse of quetiapine and olanzapine, while fairly limited in prevalence, appears to be primarily associated with under-treatment of existing medical conditions.